Electron Beam Cross-Linking of Carbon Black Filled NR/LLDPE Blends - Ahmad A.; Mohd D.Hj.; Abdullah I. (2023)
Blends of NR/LLDPE were prepared by melt blending in a Haake Rheomix at 140C with a rotor speed of 50 rpm and 15 min mixing. Liquid natural rubber (LNR) and carbon black were incorporated into the blend as a compatibilizer and filler, respectively. The effect of electron beam irradiation on the properties of carbon black filled NR/LLDPE blends has been studied over a range of radiation doses and loadings. Compared to unfilled irradiated NR/LLDPE blends, tensile strength and modulus at 100% increase with increase in the amount of the carbon black filler. Similar improvements in these properties are observed with an increase In both the radiation dose and the amount of the filler up to a certain level. The results are explained with the help of insoluble gel content and swelling index analysis. It is observed that higher reinforcement in the case of the filled samples is obtained by electron beam irradiation modification, as compared to that of using the conventional curing system.